Mizrahi Jews and the Zionist settler colonial context: between inclusion and struggle - Daniele, G. (2020)
This article intends to analyse the ‘in-between' category of Mizrahi Jews within Israeli society. The main objective is to draw attention to how Israel’s Mizrahi majority has been part of the Zionist settler colonial system itself while, at the same time, it has been greatly marginalised from the mainstream Zionist discourse led by white Ashkenazi Jews. Theoretically founded on the interconnection of three major approaches, namely settler colonialism, critical whiteness, and decolonial feminism, this contribution aims to question the current academic debate depicting asymmetric power relations founded on race, ethnic, gender and class discrimination inside Israeli society. Accordingly, Zionist settler colonialism needs to be critically analysed from a Mizrahi perspective, providing an additional element for understanding the relevance of connecting all the actors involved in the Zionist settler colonial project and reinforcing the discourse concerning settlers and indigenous people. Moreover, as the article discusses the wide cultural and political range of the Mizrahi Jews by questioning the viability of the Arab-Jew historical construct up to very recent times, it is also intended to further enhance the examination of an emerging field for studying Israel and Palestine within which several aspects and areas of inquiry remain unexplored.